Fate and transformation of silver nanoparticles in different biological conditions - Pem, Barbara; Ćurlin, Marija; Domazet Jurašin, Darija; Vrček, Valerije; Barbir, Rinea; Micek, Vedran; Fratila, Raluca M.; de la Fuente, Jesus M.; Vinković Vrček, Ivana (Beilstein Journal of Nanotechnology, 2021)
The exploitation of silver nanoparticles (AgNPs) in biomedicine represents more than one third of their overall application. Despite their wide use and significant amount of scientific data on their effects on biological systems, detailed insight into their in vivo fate is still lacking. This study aimed to elucidate the biotransformation patterns of AgNPs following oral administration. Colloidal stability, biochemical transformation, dissolution, and degradation behaviour of different types of AgNPs were evaluated in systems modelled to represent biological environments relevant for oral administration, as well as in cell culture media and tissue compartments obtained from animal models. A multimethod approach was employed by implementing light scattering (dynamic and electrophoretic) techniques, spectroscopy (UV–vis, atomic absorption, nuclear magnetic resonance) and transmission electron microscopy. The obtained results demonstrated that AgNPs may transform very quickly during their journey through different biological conditions. They are able to degrade to an ionic form and again reconstruct to a nanoparticulate form, depending on the biological environment determined by specific body compartments. As suggested for other inorganic nanoparticles by other research groups, AgNPs fail to preserve their specific integrity in in vivo settings.
Keywords: animal tissue; biological media; nanoparticle aggregation; nanoparticle dissolution; nanoparticle reformation; silver nanoparticles